2015
DOI: 10.1007/s11368-015-1111-9
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of geological and statistical approaches to element selection for sediment fingerprinting

Abstract: Purpose: Elevated sediment loads reduce reservoir capacity and significantly increase the cost of 25 operating water treatment infrastructure making the management of sediment supply to reservoirs of 26 increasing importance. Sediment fingerprinting techniques can be used to model the relative contributions of different sources of sediment accumulating in reservoirs. The goal of this research is 28 to compare geological and statistical approaches to element selection for sediment fingerprinting 29 modelling. 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…In addition to modeling and monitoring studies, the sediment fingerprinting technique was shown to provide a powerful tool to identify sediment sources in Brazil (Miguel, Dalmolin, Pedron, Moura‐Bueno, & Tiecher, ; Minella, Merten, Reichert, & dos Santos, ; Minella, Merten, Walling, & Reichert, ; Minella, Walling, & Merten, , ; Tiecher et al, ; Tiecher, Caner, et al, ; Tiecher, Caner, Minella, & dos Santos, ; Tiecher, Caner, Minella, Bender, & dos Santos, ; Tiecher, Minella, et al, ) and elsewhere in the world, such as in France (Foucher et al, ; Legout et al, ; Navratil, Evrard, Esteves, Legout, et al, ; Poulenard et al, ), Mexico (Evrard et al, ), South Africa (Foster, Boardman, & Keay‐Bright, ), Zambia (Walling, Collins, Sichingabula, & GJL, ), Canada (Barthod et al, ; Koiter et al, ; Stone, Collins, Silins, Emelko, & Zhang, ), United States (Devereux, Prestegaard, Needelman, & Gellis, ), United Kingdom (Collins, Walling, Webb, & King, ; Pulley, Foster, & Antunes, ; Smith & Blake, ), Spain (Brosinsky, Foerster, Segl, & Kaufmann, ), Luxemburg (Martínez‐Carreras et al, ), Turkey (D'Haen et al, ), Tunisia (Ben Slimane et al, ), Iran (Haddadchi, Nosrati, & Ahmadi, ), and Australia (Laceby, McMahon, Evrard, & Olley, ; Olley, Burton, Smolders, Pantus, & Pietsch, ; Wilkinson, Hancock, Bartley, Hawdon, & Keen, ). Therefore, the objective of the current study is to quantify the contribution of sources supplying sediment to the river in a catchment characterized by the widespread implementation of NT since the 1990s in Southern Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to modeling and monitoring studies, the sediment fingerprinting technique was shown to provide a powerful tool to identify sediment sources in Brazil (Miguel, Dalmolin, Pedron, Moura‐Bueno, & Tiecher, ; Minella, Merten, Reichert, & dos Santos, ; Minella, Merten, Walling, & Reichert, ; Minella, Walling, & Merten, , ; Tiecher et al, ; Tiecher, Caner, et al, ; Tiecher, Caner, Minella, & dos Santos, ; Tiecher, Caner, Minella, Bender, & dos Santos, ; Tiecher, Minella, et al, ) and elsewhere in the world, such as in France (Foucher et al, ; Legout et al, ; Navratil, Evrard, Esteves, Legout, et al, ; Poulenard et al, ), Mexico (Evrard et al, ), South Africa (Foster, Boardman, & Keay‐Bright, ), Zambia (Walling, Collins, Sichingabula, & GJL, ), Canada (Barthod et al, ; Koiter et al, ; Stone, Collins, Silins, Emelko, & Zhang, ), United States (Devereux, Prestegaard, Needelman, & Gellis, ), United Kingdom (Collins, Walling, Webb, & King, ; Pulley, Foster, & Antunes, ; Smith & Blake, ), Spain (Brosinsky, Foerster, Segl, & Kaufmann, ), Luxemburg (Martínez‐Carreras et al, ), Turkey (D'Haen et al, ), Tunisia (Ben Slimane et al, ), Iran (Haddadchi, Nosrati, & Ahmadi, ), and Australia (Laceby, McMahon, Evrard, & Olley, ; Olley, Burton, Smolders, Pantus, & Pietsch, ; Wilkinson, Hancock, Bartley, Hawdon, & Keen, ). Therefore, the objective of the current study is to quantify the contribution of sources supplying sediment to the river in a catchment characterized by the widespread implementation of NT since the 1990s in Southern Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…This model simulation and solving process was repeated 2,500 times with the median proportional source contribution from these 2,500 simulations reported as the contribution of each source. Model uncertainties were determined through the sum of the modelled SD, the median absolute deviation of the modelled source contribution and the median absolution deviation of the modelled SD for the 2,500 simulations (Laceby et al ., ). Results are presented using the notation ± to express the standard error associated with one sample whereas the mean and SD are used for groups of samples.…”
Section: Methodsmentioning
confidence: 99%
“…Often, sediment fingerprinting studies rely on the discrimination of potential sediment sources according to land use (e.g. cropland, channel bank, road, pasture and damaged roads) (Collins et al, 2012;Sherriff et al, 2015) or catchment geology (Evrard et al, 2011;Hughes et al, 2009;Laceby et al, 2015). Recently, a geochemical fingerprinting approach was used to apportion sediment sources based on catchment soil types (Lepage et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Model uncertainty was calculated by summing the standard deviation of each source's relative contribution, the modelled median absolute deviation (MAD) of these contributions, and the MAD of the modelled standard deviation for the 2500 model simulations (Laceby et al, 2015a). Paired two-tailed t-tests or Wilcoxon signedrank tests compare source contribution results derived from modelling different organic properties (i.e.…”
Section: Statistical Analyses and Source Modellingmentioning
confidence: 99%